2010
DOI: 10.1037/a0020958
|View full text |Cite
|
Sign up to set email alerts
|

Goal-directed aiming: Two components but multiple processes.

Abstract: This article reviews the behavioral literature on the control of goal-directed aiming and presents a multiple-process model of limb control. The model builds on recent variants of Woodworth's (1899) two-component model of speed-accuracy relations in voluntary movement and incorporates ideas about dynamic online limb control based on prior expectations about the efferent and afferent consequences of a planned movement. The model considers the relationship between movement speed and accuracy, and how performers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
321
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 354 publications
(353 citation statements)
references
References 177 publications
(463 reference statements)
28
321
0
4
Order By: Relevance
“…Referring to the multiple processes model (Elliott et al 2010), the play-it-safe strategy could be implemented by formation of internal representations of longer movement time, shorter movement displacements, and lower movement speed during both movement initiation and homing-in phase. The fact that increased movement time and homing-in durations were accompanied by increased number of corrective submovements in all four groups suggests that the play-it-safe strategy was adopted as a default strategy when visual feedback was withdrawn.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Referring to the multiple processes model (Elliott et al 2010), the play-it-safe strategy could be implemented by formation of internal representations of longer movement time, shorter movement displacements, and lower movement speed during both movement initiation and homing-in phase. The fact that increased movement time and homing-in durations were accompanied by increased number of corrective submovements in all four groups suggests that the play-it-safe strategy was adopted as a default strategy when visual feedback was withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…According to the multiple-process model of limb control (Elliott et al 2010), manual aiming movements generally consist of two consecutive phases: a primary movement and a homing-in phase. The primary movement corresponds to the initial pulse toward the vicinity of target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abrams et al 1990;Binsted et al 2001), thus indicating that the hand movement is planned and initiated on the basis of peripheral visual information, in conjunction with feedforward information from ocular motor command (Desmurget and Grafton 2000; Prablanc et al 1979a, b). Then, contrary to single-target aiming tasks, where foveal visual feedback plays an important role in the latter phase of the movement as the hand approaches the target (for a review, see Elliott et al 2010), in sequential aiming or object manipulation tasks, gaze is often found to shift to the next point of interest before the preceding hand movement has been completed (e.g. Helsen et al 2004;Johansson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…According to Neggers and Bekkering, this 'gaze anchoring strategy', characterized by the inhibition of a saccadic shift during an ongoing hand movement, facilitates online control using foveal vision of the hand as it approaches the target (Elliott et al 2010). However, rather than being in direct opposition, it is possible that 'gaze anchoring' Bekkering 2000, 2001) and 'buffering' (Wilmut et al 2006) reflect two modes of the visuo-motor system, which operate under different task constraints.…”
Section: Introductionmentioning
confidence: 99%